2021
DOI: 10.3390/cells10061563
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Maternal Age Deteriorates the Developmental Competence of Vitrified Oocytes in Mice

Abstract: Advanced maternal age (AMA) is known to be related to the decrease in the quality and quantity of oocytes. Oocyte vitrification is now considered an established assisted reproductive technology for fertility preservation. However, it remains unclear whether the oocytes in older women are more sensitive to various insults during vitrification. Thus, we evaluated whether AMA affects cellular and molecular features and developmental outcomes of oocytes after vitrification in mice. The oocytes were grouped as youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Oocyte vitrification and thawing were perfomred according to the methods described in ref. 49 and 50 with minor modifications. Briefly, the oocytes were placed in equilibration solution (7.5% ethylene glycol (EG), 7.5% DMSO, 20% BSA in M2 medium) for 3 min and then transferred to vitrification solution (15% EG, 15% DMSO, 0.5 M Sucrose in M2 medium) for 60 s. Finally, the oocytes were transferred to a cryovial and then immediately plunged into LN2 and stored in the LN2 tank for 0.25 hours or 0.5 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Oocyte vitrification and thawing were perfomred according to the methods described in ref. 49 and 50 with minor modifications. Briefly, the oocytes were placed in equilibration solution (7.5% ethylene glycol (EG), 7.5% DMSO, 20% BSA in M2 medium) for 3 min and then transferred to vitrification solution (15% EG, 15% DMSO, 0.5 M Sucrose in M2 medium) for 60 s. Finally, the oocytes were transferred to a cryovial and then immediately plunged into LN2 and stored in the LN2 tank for 0.25 hours or 0.5 hours.…”
Section: Methodsmentioning
confidence: 99%
“…In cryopreserved oocytes, the distribution and dynamics of mitochondria are disturbed, and the membrane potential is lowered, resembling the condition of aged oocytes [ 47 ]. It has also been reported that human and animal oocytes’ mitochondrial structure and function are seriously diminished following cryopreservation [ 17 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, higher SR (92-98%) of vitrified-warmed oocytes using the combination of EG plus DMSO, and sucrose as cryoprotectants were reported in B6D2F1 mice ( Gomes et al ., 2008 ; Zhou et al ., 2016 ). In C57BL/6J strain, Lee et al . (2021) reported a SR of 94.2% of vitrified-warmed oocytes.…”
Section: Discussionmentioning
confidence: 99%